2019
DOI: 10.1177/1098300719851226
|View full text |Cite
|
Sign up to set email alerts
|

Tootling in an After-School Setting: Decreasing Antisocial Interactions in At-Risk Students

Abstract: This study was designed to extend the research on tootling interventions, which involves reinforcing students’ reporting of their peers’ incidental prosocial behaviors. Specifically, a withdrawal design was used to determine if a tootling intervention decreased antisocial/disrespectful interactions of four, teacher-nominated students in an after-school, third-grade classroom. Visual analysis of a repeated-measures graph and effect size estimates suggested that the tootling intervention decreased these interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…One reason researchers developed the Tootling intervention was to influence students to focus on their classmates’ day-to-day prosocial behaviors, as opposed to monitoring and reporting classmates’ antisocial behaviors (Skinner et al, 2000). This enhanced awareness of classmates’ prosocial behaviors, as opposed to any increases in the students’ performance of these prosocial behaviors, could account for Tootling intervention outcomes including reductions in antisocial behaviors and increases in academic engagement (e.g., Kirkpatrick et al, 2019; Lum et al, 2019). Wright et al (2021) extended research on Tootling by demonstrating that a modified Tootling intervention increased the performance of the behaviors that students were reinforced for reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason researchers developed the Tootling intervention was to influence students to focus on their classmates’ day-to-day prosocial behaviors, as opposed to monitoring and reporting classmates’ antisocial behaviors (Skinner et al, 2000). This enhanced awareness of classmates’ prosocial behaviors, as opposed to any increases in the students’ performance of these prosocial behaviors, could account for Tootling intervention outcomes including reductions in antisocial behaviors and increases in academic engagement (e.g., Kirkpatrick et al, 2019; Lum et al, 2019). Wright et al (2021) extended research on Tootling by demonstrating that a modified Tootling intervention increased the performance of the behaviors that students were reinforced for reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers showed that implementing Tootling in classrooms can also increase on-task behavior and decrease calling out and out-of-seat behavior (Cihak et al, 2009;Lambert et al, 2015;Lum et al, 2019;McHugh et al, 2016). Kirkpatrick et al (2019) found that a Tootling intervention decreased students' antisocial interactions (i.e., mean and disrespectful behaviors).…”
mentioning
confidence: 99%
“…S-H-S behavior captures a broad array of prosocial behaviors, in the same manner that students report a broad array of antisocial behaviors (e.g., name-calling, being out of seat, cheating) when tattling. Indeed, researchers have found that having students report S-H-S behaviors while Tootling decreased disruptive classroom behaviors and social aggression (Kirkpatrick et al, 2019;Lambert et al, 2015;Lum et al, 2017Lum et al, , 2019McHugh et al, 2016).…”
Section: Select the Prosocial Behaviorsmentioning
confidence: 99%
“…Which scale is selected may depend upon goal or context. For example, Kirkpatrick et al (2019) based their criteria on the number of different students who were reported to have engaged in a prosocial behavior. They selected this scale, rather than the total number of instances of prosocial behavior, because they were concerned that students would continually report the behavior of the same student(s) (e.g., popular students who engaged in high rates of prosocial behavior) while failing to report the prosocial behaviors of less popular students.…”
Section: Criteria Scale: How Criteria Are Calculatedmentioning
confidence: 99%
“…As with numerical criteria, there are numerous ways to scale or calculate criteria. Although class averages may be the most common (Little et al., 2015), others have used criteria based on the number of desired responses meeting a cumulative criterion, the percentage of students who met a criterion, the group’s highest score, the lowest score from the group, and the average score of a randomly selected subgroup of students (Aloisio, 2006; Cashwell et al., 2001; Kirkpatrick et al., 2019; Skinner, 2008). Which scale is selected may depend upon goal or context.…”
Section: Guidelines For Developing a Pool Of Rewards And Criteriamentioning
confidence: 99%